Determining Nomophobia and Netlessphobia Levels in Gifted and Talented Children - Sureyya Nur; Canan Birimoglu Okuyan; Songul Caglar; Nilgun Kose (Acta Scientiarum. Health Sciences, 2025)
The aim of this study is to determine the levels of nomophobia and netlessphobia in gifted and talented children. The variables of nomophobia and netlessphobia are strongly and positively correlated, r(106) = .63, p < .01. According to the ordinal logistic regression analysis, girls are 4.25 times more likely to experience nomophobia than boys (OR = 4.25, 95% CI [0.65, 2.25]). Additionally, gifted adolescents whose mothers are permanently employed are 2.62 times more likely to experience nomophobia than those whose mothers are not employed in a permanent job (OR = 2.62, 95% CI [0.16, 1.77]). Exposure to electromagnetic waves is believed to potentially cause hearing problems, brain stimulation effects, and even brain tumors. The strong correlation between nomophobia and netlessphobia highlights the risks associated with excessive digital device use. Considering the potential psychological and physiological effects, interventions that promote responsible technology use are essential.